2014
DOI: 10.3892/ijo.2014.2527
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal trefoil factor activates the PI3K/Akt signaling pathway to protect gastric mucosal epithelium from damage

Abstract: Abstract.Intestinal trefoil factor (ITF, also named as trefoil factor 3, TFF3) is a member of the TFF-domain peptide family, which plays an essential role in the regulation of cell survival, cell migration and maintains mucosal epithelial integrity in the gastrointestinal tract. However, the underlying mechanisms and associated molecules remain unclear. The aim of this study was to explore the protective effects of ITF on gastric mucosal epithelium injury and its possible molecular mechanisms of action. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…This effect is accompanied by an increased expression of the tight junction proteins ZO-1, OCCLUDIN, and CLAUDIN-1 and is reversed if TLR2 is knocked down in the Caco-2 cell (144). Effects were mediated by the PI3K/Akt pathway (144), consistent with other findings that the protective effect of TFF3 in gastric mucosal epithelial cell is mediated by activation of this signaling pathway (92). Thus, TFF3 seems able to inhibit inflammatory cytokines in addition to other cellular effects that enhance mucosal defenses.…”
Section: Trefoil Factor and Gastrointestinal Diseasessupporting
confidence: 90%
See 2 more Smart Citations
“…This effect is accompanied by an increased expression of the tight junction proteins ZO-1, OCCLUDIN, and CLAUDIN-1 and is reversed if TLR2 is knocked down in the Caco-2 cell (144). Effects were mediated by the PI3K/Akt pathway (144), consistent with other findings that the protective effect of TFF3 in gastric mucosal epithelial cell is mediated by activation of this signaling pathway (92). Thus, TFF3 seems able to inhibit inflammatory cytokines in addition to other cellular effects that enhance mucosal defenses.…”
Section: Trefoil Factor and Gastrointestinal Diseasessupporting
confidence: 90%
“…TFF peptides were demonstrated to regulate cell survival via ERK/MAPK, PI3K/Akt, phospholipase C (PLC)/PKC, β-catenin, and EGF signaling pathway (34, 78, 87, 8991). Sun et al (92) showed that in cultured GES-1 cells (normal human gastric epithelial cells), exogenous addition of TFF3 activated the PI3K/Akt pathway known to be involved in gastric epithelial repair. Given the previously noted promiscuity of TFF peptide action, results support the concept that TFF peptides are involved in GI mucusal repair, although TFF3 is normally found only in the intestine and not the stomach.…”
Section: Trefoil Factor Peptides and Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from these, TFF3 activates the PI3K/Akt signaling axis to preserve the integrity of gastric mucosal epithelium [131], as well as accelerating tumorigenesis via the Leptin/ObRb/STAT3 (signal transducers and activators of transcription 3) pathway [108] and promoting the growth and invasion of GC cells through the HIF-1α(hypoxia-inducible transcription factors-1α)/ VEGF(vascular endothelial growth factor)/ STAT3…”
Section: Othersmentioning
confidence: 99%
“…We further investigated the underlying mechanism of CCR5-mediated proliferation and invasion in U87 and U251 cells by western blot analysis. Because PI3K/Akt signaling pathway has been shown to play important roles in cell proliferation, migration, and survival [33,34], we hypothesized that Akt activation might contribute to CCR5-mediated proliferation and invasion in GBMs. To verify our hypothesis, U87 and U251 cells were treated with CCL5, PI3K inhibitor LY294002, or CCR5 siRNA.…”
Section: Involvement Of P-akt In Ccr5-mediated Proliferation and Invamentioning
confidence: 99%